2020
DOI: 10.1007/s12021-020-09461-z
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of Interneuron Morphology Representations for Cell Type Discrimination

Abstract: Quantitative analysis of neuronal morphologies usually begins with choosing a particular feature representation in order to make individual morphologies amenable to standard statistics tools and machine learning algorithms. Many different feature representations have been suggested in the literature, ranging from density maps to intersection profiles, but they have never been compared side by side. Here we performed a systematic comparison of various representations, measuring how well they were able to captur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…In addition to quantifying basic morphometric parameters, nGauge includes comprehensive utility functions for advanced neuroinformatics analysis (Table 1). For instance, nGauge implements the widely used Principal Component Analysis (PCA) to identify the differences between vectors of morphometrics (Gouwens et al, 2019;Laturnus, Kobak, et al, 2020). We performed PCA on a collection of pyramidal cells and basket cells (Miyamae et al, 2017) (Figure 5A) and a collection of tufted cells and mitral cells (Fukunaga et al, 2012) (Figure 5B).…”
Section: Performing Advanced Analysis With Ngaugementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to quantifying basic morphometric parameters, nGauge includes comprehensive utility functions for advanced neuroinformatics analysis (Table 1). For instance, nGauge implements the widely used Principal Component Analysis (PCA) to identify the differences between vectors of morphometrics (Gouwens et al, 2019;Laturnus, Kobak, et al, 2020). We performed PCA on a collection of pyramidal cells and basket cells (Miyamae et al, 2017) (Figure 5A) and a collection of tufted cells and mitral cells (Fukunaga et al, 2012) (Figure 5B).…”
Section: Performing Advanced Analysis With Ngaugementioning
confidence: 99%
“…Beyond single-value morphometrics, many tools have been integrated into nGauge for performing advanced analysis techniques. Influenced by recent work (Laturnus, Kobak, et al, 2020), nGauge includes tools to calculate 2D morphometric histograms; two example cells from (Miyamae et al, 2017) are shown (Figure 6). These plots can serve as "fingerprints" for the morphological properties of individual neurons.…”
Section: Performing Advanced Analysis With Ngaugementioning
confidence: 99%
See 1 more Smart Citation
“…Many different types of quantitative representations, such as density maps (Jefferis et al (2007); Laturnus, Kobak, and Berens (2020)), graph theory (Gillette and Grefenstette (2009); Heumann and Wittum (2009)), topology (Kanari et al (2018)), and morphometric statistics (Laturnus et al (2020); Polavaram, Gillette, Parekh, and Ascoli (2014); Uylings and van Pelt (2002)), have been applied to describe functionally different types of mature neurons. In addition, machine learning techniques also have been used for identifying neuron types (Laturnus et al (2020)) and for identifying neuronal polarity (Su et al (2021)). Laturnus et al (2020) noted the importance of the spatial extent and shape describing neuron connectivity in distinguishing cell types, instead of specific branching features.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, machine learning techniques also have been used for identifying neuron types (Laturnus et al (2020)) and for identifying neuronal polarity (Su et al (2021)). Laturnus et al (2020) noted the importance of the spatial extent and shape describing neuron connectivity in distinguishing cell types, instead of specific branching features. Although these quantitative representations can characterize neuronal cell types, most have not been applied to discriminate between neurite growth stages or time points.…”
Section: Introductionmentioning
confidence: 99%